Minimally-Invasive Approach in the Setting of a Malignant Primary Cardiac Tumor - Polat, Emre; Stock, Sina; Owais, Tamer; Girdauskas, Evaldas (The Thoracic and Cardiovascular Surgeon Reports, 2024)
A 71-year-old man with dilated cardiomyopathy without clinical complaints revealed a suspicious finding in checkup. After a multimodality cardiac imaging, the suspicion of a malignant primary cardiac tumor in the left ventricle was substantiated and the patient underwent minimally-invasive cardiac surgery for tumor resection. Postoperative chemotherapy with multiple cycles of liposomal doxorubicin was established and supported by proton beam radiotherapy. Two-year follow-up revealed no disease recurrence.
Keywords: minimally-invasive surgery; mini-thoracotomy; sarcoma; cardiovascular surgery